Diagnostic accuracy of preoperative MRI in assessing macrotrabecular-massive subtype of hepatocellular carcinoma: a systematic review and meta-analysis - Zhou, Tingwen; Han, Xiaorui; Xiao, Chuyin; Lei, Xiaoxiao; Lan, Xinxin; Wei, Xinhua; Liang, Yingying; Wu, Hongzhen (European radiology, 2025)
Objectives To determine the value of preoperative magnetic resonance imaging (MRI) in predicting macrotrabecular-massive hepatocellular carcinoma (MTM-HCC). Materials and methods A search was conducted on PubMed, Web of Science, Cochrane Library databases, and Embase for studies evaluating the performance of MRI in assessing MTM-HCC. The quality assessment of diagnostic studies (QUADAS-2) tool was used to assess the risk of bias. Diagnostic accuracy measures, including sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR), were pooled. Summary receiver operating characteristic (SROC) curves with the area under the curve (AUC) were generated. Meta-regression analysis was performed to explore potential sources of heterogeneity. Results A total of ten eligible studies including 2074 lesions in 2053 patients were analyzed. The pooled sensitivity, specificity, PLR, NLR, DOR, and AUC were 0.65 (0.52, 0.76), 0.88 (0.80, 0.94), 5.6 (3.70, 8.60), 0.40 (0.30, 0.53), 14 (10, 20), and 0.84 (0.81, 0.87), respectively. High heterogeneity was observed ( I 2 was 78.61% and 90.95% for sensitivity and specificity, respectively) along with a threshold effect (Spearman’s correlation coefficient = 0.927, p < 0.001). Meta-regression analysis demonstrated that the MRI method (radiomics or non-radiomics) affected the heterogeneity. Conclusion MRI has diagnostic value for MTM-HCC due to its higher specificity and moderate sensitivity, but its clinical application remains suboptimal due to significant heterogeneity. Thus, further prospective studies with large sample sizes are needed to confirm these results. Key Points Question What is the value of MRI for preoperatively predicting MTM-HCC ? Findings Meta-regression analyses revealed that the MRI method (radiomics or non-radiomics) is a significant factor contributing to heterogeneity . Clinical relevance This study demonstrates the high diagnostic accuracy of MRI for early detection of MTM-HCC, which can assist in guiding individualized management .